The Willingness to Adopt Local Feed Innovation Among Cattle Farmers - Putra, Ahmad Romadhoni Surya; Pratama, Indra Wahyu; Agustine, Restiyana; Astuti, Andriyani; Kasmiyati, Kasmiyati; Noviandi, Cuk Tri; Poppi, Dennis; Harper, Karen; Agus, Ali (ANIMAL PRODUCTION, 2024)
This study aimed to analyze the farmers' willingness in adopting local feed innovation and to analyze its background factors. This study involved 106 cattle farmers who lived in Arjowilangun and Kucur villages of Malang Regency, East Java. Data were collected from respondents through personal interviews with structured questionnaires. This study also used descriptive statistical analysis and Probit regression as the methods. The research results showed that most of the farmers were willing to partially adopt local feed innovation. Social and economic factors that statistically gave significant influence on the farmers' willingness in adopting the local feed innovation are age, the number of cattle, cattle agribusiness type, membership in a farmer's group, and the perception towards the cattle farming conditions. Age and the number of cattle negatively affect the farmers' willingness while membership in a farmer's group and perception towards the cattle farming conditions has a positive effect on the farmers' willingness in adopting local feed innovation. Farmers who are running the cattle fattening business have larger probabilities to reject the local feed innovation. Furthermore, optimizing coaching and assisting activities through the farmer's group can be an effective way to increase the farmers' willingness to entirely adopt the local feed innovations.